2016
DOI: 10.1021/acs.energyfuels.5b02582
|View full text |Cite
|
Sign up to set email alerts
|

CO2Reaction Mechanisms with Hindered Alkanolamines: Control and Promotion of Reaction Pathways

Abstract: The mechanisms of the reaction of CO2 with hindered alkanolamines are described based on direct reaction monitoring with in situ 13C NMR spectroscopy. Four amines of increasing steric hindrance were studied and compared with unhindered primary, secondary, and tertiary alkanolamines. The number and location of additional methyl (or other) groups on the nitrogen or adjacent carbon atoms create different degrees of steric hindrance. As steric hindrance increases, the Lewis basicity (nucleophilicity), as an affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 28 publications
1
91
0
Order By: Relevance
“…The number of sites available for adsorption drastically decreases and implies a saturation of the capacitance change. It is well known that the interaction of CO2 with the amino group containing materials is basically an acid-base reaction [11]. However, the sensing properties of these sensing materials are affected by the type of the host matrix for the amino groups.…”
Section: Resultsmentioning
confidence: 99%
“…The number of sites available for adsorption drastically decreases and implies a saturation of the capacitance change. It is well known that the interaction of CO2 with the amino group containing materials is basically an acid-base reaction [11]. However, the sensing properties of these sensing materials are affected by the type of the host matrix for the amino groups.…”
Section: Resultsmentioning
confidence: 99%
“…El Mahdy et al deduced that the better uptake efficiency of TPA-COF-2 was caused by the steric hindrance around the nitrogen atoms in the nonplanar triarylamine unit. The nucleophilicity of the nitrogen atom decreased as the steric hindrance around the nitrogen increased; which decreases the number of carbon dioxide molecules adsorbed (Kortunov et al, 2016). The same concepts can be applied to the TPT-COF series for which TPT-COF-6 had the highest CO 2 uptake capacities 65.65 and 92.38 mg g −1 at 298 and 273 K, respectively, TPT-COF-6 had six triaryltraizine units.…”
Section: Studies On Cof Structures and Composition For Optimizing Comentioning
confidence: 89%
“…Hence, the amine capacity, in terms of amount of conjugate base (DEEA), is reduced, i.e. the basicity of the amine solution is weaker, and since the concentration of CO3 2starts to be diminished, it can be concluded that CO3 2also reacts as a conjugate base, 24,46 as reported in reaction 11 (similarly to the generic reaction 4 or the DEEA-specific reaction 13).…”
Section: Chemistry Of the System And Nmr Analysismentioning
confidence: 95%